NEW ASPECTS ON THE FORMATION OF HYDROCARBON SOURCE ROCKS - Zimmerle W. (My University, 1985)
Episodic volcanism favors, as shown by examples from Europe, the USA, and Brazil, the formation of organic-rich sediments (hydrocarbon source rocks). The examples examined from Europe comprise the Lower Carboniferous Oil-Shale Group, Scotland; Upper Carboniferous Coal Measures, western Germany; Upper Jurassic Kimmeridge Shale, North Sea area; Lower Cretaceous Blättertonstein, northwest Germany; and Eocene Messel Oil Shale, Rheingraben. Examples from the USA are Devonian/Mississippian Gas Shales, Permian Phosphoria Shale, Middle Cretaceous Mowry Shale, Eocene Green River Shale, and Miocene Monterey Shale. Examples from Brazil are Permian Iratí Oil Shale and Oligocene Paraiba-Valley Oil Shale. Volcanism is reflected during sedimentation (1) by exhalation of SO2 and/or CO2, (2) volcanic ashfalls, (3) by generation of anoxia and preservation of organic matter, and (4) by halmyrolytic alteration of volcanic ashes into highly surface-active clay minerals (montmorillonite).
Keywords: Miocene; Cretaceous; Eocene; Oligocene; Carboniferous; Permian; Jurassic; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Эоцен; Paleozoic::Carboniferous; Кайнозой::Неоген::Миоцен; Paleozoic::Permian; Кайнозой::Палеоген::Олигоцен; Cenozoic::Neogene::Miocene; Мезозой::Меловая; Мезозой::Юрская; Mesozoic::Cretaceous; Палеозой::Каменноугольная; Cenozoic::Paleogene::Eocene; Mesozoic::Jurassic; Палеозой::Пермская